Make money move : a guide to financial wellness - Simmons, Lauren (Podcaster) (Amistad, an imprint of HarperCollins Publishers, 2023)
"In 2017, when she was only twenty-two, Lauren Simmons became the youngest full-time female trader at the New York Stock Exchange, and the second African American woman in the Exchange's 228-year history to hold such a position. Driven by a passion for empowering women, Millennials, Gen Zs, and minorities to become more financially savvy, she now shares her experience and knowledge in this savvy financial guide. Simmons brings a fresh perspective to personal finance: she is a young African American woman with an understanding of how to increase wealth and an awareness of generational and cultural barriers--such an income inequity--that can hold people back from taking financial risks. In her warm, down-to-earth voice, Simmons makes confusing topics easy to understand. She breaks down the pros and cons of buying stocks and Treasuries, explains how to maximize your 401K opportunities even in challenging economic times, advises how to grapple with student loans, and helps you break family cycles when dealing (or not) with debt"--